2013
DOI: 10.1007/s00330-013-3027-3
|View full text |Cite
|
Sign up to set email alerts
|

Low-tube-voltage (80 kVp) CT aortography using 320-row volume CT with adaptive iterative reconstruction: lower contrast medium and radiation dose

Abstract: • CT aortography at 80 kVp allows a significant reduction in radiation dose. • Addition of iterative reconstruction reduces image noise and improves image quality. • The injected contrast medium dose can be substantially reduced at 80 kVp. • Aortic enhancement is uniform despite a reduced volume of contrast medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…2 Previous studies have shown that a reduction of the tube potential in CT angiography (CTA) can result in higher intravascular iodine enhancement with reduced radiation dose in comparison with standard protocols with a higher tube voltage. [3][4][5][6][7][8][9][10][11] Low tube potential CT protocols in clinical routine are, however, limited by the maximum available tube current time product, since high tube currents are necessary to counterbalance the reduced photon generation efficiency of the tube and the lower X-ray energy, especially in patients who are overweight and obese. Since low tube potential scanning is generally limited by the maximum achievable tube current, time product the simultaneous acquisition dual-source scanning mode appears promising for use in low-peak kilovoltage (kVp) scanning, especially in patients who are bigger.…”
Section: Introductionmentioning
confidence: 99%
“…2 Previous studies have shown that a reduction of the tube potential in CT angiography (CTA) can result in higher intravascular iodine enhancement with reduced radiation dose in comparison with standard protocols with a higher tube voltage. [3][4][5][6][7][8][9][10][11] Low tube potential CT protocols in clinical routine are, however, limited by the maximum available tube current time product, since high tube currents are necessary to counterbalance the reduced photon generation efficiency of the tube and the lower X-ray energy, especially in patients who are overweight and obese. Since low tube potential scanning is generally limited by the maximum achievable tube current, time product the simultaneous acquisition dual-source scanning mode appears promising for use in low-peak kilovoltage (kVp) scanning, especially in patients who are bigger.…”
Section: Introductionmentioning
confidence: 99%
“…The dose of a CT scan depends on the settings of factors, such as the scout view, the scan length, exposure settings, type of scanning, slice thickness and pitch values. Now, contrast‐enhanced CT with a low tube voltage technique is widely used for reducing the radiation dose and the iodine load …”
Section: Discussionmentioning
confidence: 99%
“…Thus, we have to choose appropriate examination protocols in the paediatric CT scan, following the ALARA principle (As Low As Reasonably Achievable) for applying both the radiation and the contrast agent. In the last decade, the CT with a low tube voltage technique has been widely used for reducing the radiation dose …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Oda et al [50], CT venography with a lower tube potential technique (80 vs 120 kV) allowed reduction in contrast volume from 150 to 100 mL without degradation of image quality. More recent studies have shown that CT performed with a low tube potential and low contrast dose with iterative reconstruction has better or equivalent contrast enhancement and image quality than CT performed with standard tube potential and a standard contrast dose with a traditional reconstruction algorithm [51][52][53][54]. Nakaura et al [53] evaluated the effect of a low contrast and low radiation dose protocol on image quality in cardiac CT using a low tube potential (80 vs 120 kV), a hybrid iterative reconstruction algorithm, and a 256-MDCT scanner.…”
Section: Comparison With Existing Literature Findingsmentioning
confidence: 99%